2008
DOI: 10.1542/peds.2007-1172
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Growth and Cognitive Abilities at 56 Months of Age: A Longitudinal Study of Infants Born at Term

Abstract: Our findings suggest that, even within the range of children born at term, prenatal and postnatal growth in body size are associated with individual differences in cognitive abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
107
2
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 32 publications
8
107
2
8
Order By: Relevance
“…An earlier analysis of the ALSPAC 10% substudy 14 and 1 other study 15 found that head growth during infancy was associated with IQ, but the observed IQ variation in these studies was small and all of the children studied were within the normal range.…”
Section: Discussionmentioning
confidence: 85%
“…An earlier analysis of the ALSPAC 10% substudy 14 and 1 other study 15 found that head growth during infancy was associated with IQ, but the observed IQ variation in these studies was small and all of the children studied were within the normal range.…”
Section: Discussionmentioning
confidence: 85%
“…[3][4][5][6][7] One recent report of critical periods found a strong association between postnatal head growth at 9 months and cognitive functioning at age 9 years, but no relation between head circumference in gestation or at birth with later neurodevelopmental outcomes at age 9 years. 8 Other studies have shown that small head circumference at birth can also predict poor intellectual performance in childhood and adulthood, 9,10 although this relationship appears to depend on the particular cognitive domain. 11 Head circumference is considered the most sensitive anthropometric measure of long-term malnutrition in infancy, 12,13 with caloric deprivation shown to be directly associated with suboptimal head growth.…”
Section: Introductionmentioning
confidence: 99%
“…7,28 Studies of postnatal growth and cognitive or behavioral outcomes have focused on weight gain in the first 5 to 12 months of life, not specifically in the neonatal period. [4][5][6][7][8] In general, more rapid postnatal growth among healthy term-born children is linked to better cognitive outcomes. In one of the few studies that explored the early postnatal period, Emond et al 3 showed that children with the lowest 5% of weight gain from birth to 8 weeks had ∼3-point lower IQ scores than the rest of the cohort (n = 7975).…”
Section: Discussionmentioning
confidence: 99%
“…At the extreme, infants with feeding difficulties may be diagnosed with growth faltering (or "failure to thrive"), which has been associated with 3-to 4-point lower IQ scores compared with children without growth faltering. 2,3 Previous studies in nonclinical populations suggest that faster growth in infancy and childhood is associated with better cognitive outcomes, [4][5][6][7][8] although some findings have been null. 9 Disparities in the literature may reflect varying methods of analysis, small sample sizes (resulting in insufficient statistical power), and differences in the age period studied.…”
mentioning
confidence: 99%